A Nationwide Assessment of the Biodiversity Value of Uganda's Important Bird Areas Network - HERBERT TUSHABE; JAMES KALEMA; ACHILLES BYARUHANGA; JOSEPHINE ASASIRA; PAUL SSEGAWA; ANDREW BALMFORD; TIM DAVENPORT; JON FJELDSÅ; IB FRIIS; DEBORAH PAIN; DEREK POMEROY; PAUL WILLIAMS; et al. (Conservation Biology, 2006)
BirdLife International's Important Bird Areas (IBA) program is the most developed global system for identifying sites of conservation priority. There have been few assessments, however, of the conservation value of IBAs for nonavian taxa. We combined past data with extensive new survey results for Uganda's IBAs in the most comprehensive assessment to date of the wider biodiversity value of a tropical country's IBA network. The combined data set included more than 35,000 site × species records for birds, butterflies, and woody plants at 86 Ugandan sites (23,400 km 2 ), including 29 of the country's 30 IBAs, with data on additional taxa for many sites. Uganda's IBAs contained at least 70% of the country's butterfly and woody plant species, 86% of its dragonflies and 97% of its birds. They also included 21 of Uganda's 22 major vegetation types. For butterflies, dragonflies, and some families of plants assessed, species of high conservation concern were well represented (less so for the latter). The IBAs successfully represented wider biodiversity largely because many have distinctive avifaunas and, as shown by high cross‐taxon congruence in complementarity, such sites tended to be distinctive for other groups too. Cross‐taxon congruence in overall species richness was weaker and mainly associated with differences in site size. When compared with alternative sets of sites selected using complementarity‐based, area‐based, or random site‐selection algorithms, the IBA network was efficient in terms of the number of sites required to represent species but inefficient in terms of total area. This was mainly because IBA selection considers factors other than area, however, which probably improves both the cost‐effectiveness of the network and the persistence of represented species.